Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio in Poststroke Depression: A Systematic Review and Meta-Analysis. (8th August 2022) - Sarejloo, Shirin; Abadifard, Erfan; Othman, Zhian Jamal; Zafarani, Fatemeh; Khanzadeh, Monireh; Sadigh-Eteghad, Saeed; Farajdokht, Fereshteh; Mohammadpoorasl, Asghar; Khanzadeh, Shokoufeh
Abstract : Objectives . Evidence shows that stroke-induced inflammatory responses play an essential role in the development of poststroke depression (PSD). The goal of this systematic review and meta-analysis was to critically evaluate the literature regarding the use of the neutrophil to lymphocyte ratio (NLR) as a reliable means to detect early PSD development, to help clinicians institute early interventions and improve outcomes. Methods . Electronic databases, including Web of Science, PubMed, Google Scholar, and Scopus, were searched, and eight studies were included. We assessed the certainty of the associations with GRADE methods. Results . We found that patients with PSD had higher NLR than the stroke patients with no depression (SMD = 0.51 ; CI   95 % = 0.29 -0.73, p < 0.001 ). Also, we found a significantly higher PLR in the patients with PSD when compared to the stroke patients with no depression (SMD = 0.66 ; CI   95 % = 0.19 -1.13, p < 0.001 ). Conclusion . These findings indicated that NLR and PLR could be considered inexpensive biomarkers for the prediction of PSD.